Fragmentation of a molten metal droplet in an ambient water flow - Cunningham, Mark H.; Frost, David L. (Frontiers in Physics, 2023)
The influence of an ambient fluid flow on the fragmentation of hot molten tin droplets (initially at 800°C) and cold low melting point alloy droplets (initially at 70°C) in water is investigated with high-speed photography and flash radiography. The water is accelerated using a converging nozzle to a constant speed of up to 30 m/s using a double piston arrangement designed to eliminate the formation of a shock wave that is present in most earlier studies. At low flow velocities, the fragmentation of hot droplets is governed by thermal effects and vapour formation, growth, and collapse. At high flow velocities, vapour formation is suppressed and the droplet fragmentation is determined by hydrodynamic effects in which hydrodynamic instabilities (Rayleigh-Taylor and Kelvin-Helmholtz) and wavecrest stripping all play a role in the droplet breakup. At intermediate flow velocities, both thermal and hydrodynamic effects play a role. Quantitative image analysis of the radiographs is used to determine the spatial distribution of the droplet mass during the fragmentation process. Comparison with earlier work in which the ambient flow is preceded by a strong shock wave indicates that the transition from thermal to hydrodynamic breakup is strongly dependent on the pressure field.